Sittlichkeit und Politik: § 175 im Zweiten Deutschen Reich : (1871-1919) - Taeger, Angela (Kriminologische Forschung in den 80er Jahren ; [3,2], 1988)
The research project investigates the legislative processes referring to male homosexuality (§ 175 of the German Penal Code). In 1871 the prescription was transmitted from the Prussian Penal Code of 1851. 1909, within a revision of the code it was planned to introduce a more severe norm. We collected all available sources in West· and Eastern German archives. The article establishes a strong relation between the general political structure and this example of a legislation of morality. In 1871 the Reich was founded; the strict laws in (homo-)sexual matters helped to unify heterogeneous law traditions into the nation state. Prussianism and nationalism were its primary features. In 1909 the personal regime of the Emperor had just survived a serious crisis after several friends of the Kaiser had been named as homosexuals. His masculinity as well as his moral integrity had to be proven. Discussing antihomosexual laws was part of his strategy: - however, the end of the regime was already approaching.